Global existence of solution for Monge–Ampére equation with an external periodic force on 3-dimensional torus. (August 2020) - Li, Liangchen; Zhao, Xin
Abstract: This paper is devoted to construction of a non-convex global solution for Monge–Ampére equation with an external periodic force on 3-dimensional torus. More precisely, we show that this non-convex solution is a periodic solution, which is unique in a ball with radius 1.